La tipificación del contrato de franquicia como alternativa para impulsar el desarrollo de empresas peruanas en el mercado local - Speicher Mendiola, Cristhina Giselle (2022)
The franchise is considered a business model that allows the franchisor to expand it to other geographical areas through the capital contribution of the franchisee in exchange for granting a license to the brand and the transfer of the franchise's know-how. Peruvian franchises have had a constant growth in our national market that contributes to the country’s GDP and to the employment offer. It is growth could be better if the franchise contract had a contract regulation, in order to reduce the gaps of uncertainty and conflicts between the parties that usually appear in the negotiation and execution stages of the contract. Finally, for the development of this thesis, the qualitative research methodology has been used, which will allow us, through surveys and interviews to franchisors and franchisees, to determine the positive impact that the classification of the franchise contract would bring to Peru.